Alo-transplante parcial de bexiga em cães (Canis familiaris): avaliação clínica, histológica e imunoistoquímica - Marcelo Weinstein Teixeira (2007)
The hypothesis that the bladder partially allotransplantation in dogs, develop the structural and functional capacity of this organ was tested. Twenty healthy dogs (10 of male gender and 10 of female) were submitted to an experimental cystectomy, with a withdrawal between 70 and 80% of the organ and preservation of the vesical trigone. The fresh alotransplant was used in the reconstruction of the urinary vesicle and the animals were watched during 180 days. At the eighth day of postoperative, they showed urinary contention capacity and spontaneous urination. There was a gradual growth of the urinary vesicle volume, reaching at the 120th days of postoperative similar values of the ones determined before the surgery. The transplanted tissue acted as a substratum for the migration of vesical tissue, permitting the bladder growth and gradual increase of the organ volumetric capacity. Histhologically the regeneration of all the bladder layers during the study time was observed. The expression immunohistochemistry of the protein TGF1 had been involved in the differentiation process of the urotelium and AML in the repair of the conjunctive tissue process. It is concluded that the bladder alotransplant is viable, develop the repletion capacity and others physiological functions of the urinary vesicle